Forming spiritual culture of future teachers of physical education - Zolochevskiy V.V; Roschenko O.O (Kharkov National Pedagogical University, 2010)
The necessity of forming spiritual culture of future teachers of physical education of musical rhythmic employments facilities is grounded. Is shown the necessity of construction of teaching and educational process of preparation future teachers on a basis of update and orientation of maintenance on development of culture of thought. A purpose, tasks, maintenance and method of teaching of course of ритмики and choreography, is certain. The special course is offered "Method of musical rhythmic employments at school". The special course is rendered by an assistance the increase of level of professional preparation of future teachers to the leadthrough musically-rhythmic employments on the lessons of physical culture at school.